Chemical Oxygen Demand Removal in Na2SO4 Saturated Wastewater by Cultivable Halotolerant Bacterial Community. Issue 6 (3rd May 2016) - Zhang, Wen Wu; Pan, Jie; Hao, Peng Ying; Zhen, Gang; Zhang, Zhen Li; Wu, Min
Abstract : Industrial wastewater with a high Na2 SO4 concentration is characterized by high osmotic pressure and salinity, and requires pretreatment before discharging into central treatment facilities. To date, few studies have addressed the chemical oxygen demand (COD) removal in biotreatment of Na2 SO4 wastewater. Here, a novel aerobic system for treating Na2 SO4 wastewater was developed based on screening halotolerant bacterial strains. The system maintained a stable COD removal at >90% in saturated concentration (varying from 5 to 40% depending on the temperature) of Na2 SO4 for 5 years. Activated sludge was initially constructed by cultured strains of Hyphomicrobium sp. CB03, Dietzia sp. XM15, Staphylococcus sp. T211, Flavobacterium sp. AXY1, Ochrobactrum sp. BY4, Bacillus sp. BYXT, Sphingobacterium sp.YY1, Rhodococcus sp. NH7‐4, Stappia sp. HM4, Microbacterium sp. PY3‐1, and Pseudomonas sp. MN3‐2. Uncultured phylum TM7 was detected in the sludge after acclimatization. The present aerobic cultivable halotolerant bacterial community was successfully applied to large scale removal of organic pollutants in saline wastewater. Abstract : A simple biotreatment system was started to treat sewage with saturated Na2 SO4 . It achieved a removal rate of >90% COD for years. Halotolerant bacteria were the key of the system. These culitvable bacteria, including 11 species, were isolated from several salinity samples. This method could be applied to similar sewage with biodegradable compounds and high sulfate.